Public employment and women: the impact of Argentina's Jefes Program on female heads of poor households - Pavlina R. Tcherneva; L. Randall Wray (Levy Economics Institute of Bard College, 2007)
In 2002, Argentina implemented a large-scale public employment program to deal with the latest economic crisis and the ensuing massive unemployment and poverty. The program, known as Plan Jefes, offered part-time work for unemployed heads of households, and yet more than 70 percent of the people who turned up for work were women. The present paper evaluates the operation of this program, its macroeconomic effects, and its impact on program participants. We report findings from our 2005 meetings with policymakers and visits to different project sites. We find that Jefes addresses many important community problems, is well received by participants, and serves the needs of women particularly well. Some of the benefits women report are working in mother-friendly jobs, getting needed training and education, helping the community, and finding dignity and empowerment through work.
Keywords: E65; I38; J16; J68; O84; 330; Argentina; Jefes y Jefas; Public Employment; Women